Constructing success in global health: the World Bank and the Onchocerciasis Control Programme in West Africa - Winters, Janelle Kathleen (The University of Edinburgh, 2020)
The Onchocerciasis Control Programme in West Africa (OCP), a United Nations-sponsored initiative that targeted a neglected tropical disease (NTD) from 1974-2002, has been depicted as a major global health success story since the late 1980s. The programme’s fiscal agency (the World Bank) and executing agency (the World Health Organization) have been vocal in their praise for the programme, which is often put forward as a model disease control and development initiative. This dissertation uses the World Bank’s role in the OCP as a case study for how success is defined and operationalised by global health institutions. It explores three inter-related questions: in what ways and by what definition has the OCP been seen as a success by the Bank and the global health community, what complexities does the Bank’s success narrative overlook, and how does the OCP success narrative relate to frameworks of success used by global health researchers and policymakers? Using global health governance and history methodologies – including a literature review of ‘success’ and the OCP, an analysis of development assistance for health financial flows, oral history interviews, and in-depth archival research at six sponsoring agency and donor institutions – I identify four major components of the Bank’s ‘dominant’ success narrative. These include clear objectives and metrics; sound extra-budgetary financial management; strong partnership among sponsoring agencies, donors, and the private sector; and community-based delivery mechanisms. I then describe the complexities of programme operation (‘underlying narratives’) for each of these components. Finally, I discuss the legacy of the OCP’s success, in terms of the Bank’s role in global health governance. I engage with four major themes in global health governance to explain the appeal of the OCP dominant narrative. First, the metrics used to justify the OCP’s success are the product of significant assumptions, which themselves reflect the Bank’s heavily politicised ideologies of human capital and efficiency. Second, the OCP showcases the Bank and WHO’s growing reliance on globally-focused trust funds, which allow these institutions to argue that they are ‘catalysing’ novel investments in global health. Third, the rise of public-private partnerships (PPPs) in global health reflects this controversial embrace of cost-effectiveness, catalytic aid, and private philanthropy. Fourth, the Bank and other multilateral institutions’ emphasis on community-based delivery mechanisms for the integrated control of NTDs embraces a ‘selective’ definition of primary health care and health system strengthening. Ultimately, I argue that success in global health is constructible. It is non-absolute, contestable, and inseparable from the ideologies of influential institutions. I conclude with a discussion of mechanisms by which success is constructed in global health, including visual politics and active marketing techniques.
Keywords: global health; World Bank; success; history of medicine; governance; neglected tropical diseases; health policy; Onchocerciasis